2009
DOI: 10.1590/s0102-09352009000600010
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos morfológicos, morfométricos e ultraestruturais do baço de ratos após o clampeamento total do pedículo hepático

Abstract: RESUMOAvaliaram-se as alterações morfológicas, morfométricas e ultraestruturais que ocorreram no baço devido à isquemia produzida pelo clampeamento total do pedículo hepático. Para tanto, foram utilizados 40 ratos machos, distribuídos em quatro grupos de 10 animais. O grupo-controle (C) não foi submetido à isquemia, e os grupos tratados (E 1 , E 2 e E 3 ) foram submetidos ao clampeamento por 10, 20 e 30 minutos, respectivamente. Fragmentos do baço foram retirados e analisados histologicamente pela microscopia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Intestinal ischemia insult tolerance can also vary according to the different species. Experimental studies in rats and mice showed histopathological alterations in ischemic situations lasting for 30 minutes (Guimarães et al 2002, Freitas et al 2009a, 2009b; 45 minutes (Jiang et al 2011. ); 15 and 50 minutes (Guan et al 2009) and 60 minutes (Boybeyi et al 2014) whereas for dogs the ischemic time was 60 minutes (Chiu et al 1970), for rabbits starting at 60 minutes (Gao et al 2006) and horses starting at 70 minutes (Dabareiner et al 2001) and 120 minutes (Pagliosa et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal ischemia insult tolerance can also vary according to the different species. Experimental studies in rats and mice showed histopathological alterations in ischemic situations lasting for 30 minutes (Guimarães et al 2002, Freitas et al 2009a, 2009b; 45 minutes (Jiang et al 2011. ); 15 and 50 minutes (Guan et al 2009) and 60 minutes (Boybeyi et al 2014) whereas for dogs the ischemic time was 60 minutes (Chiu et al 1970), for rabbits starting at 60 minutes (Gao et al 2006) and horses starting at 70 minutes (Dabareiner et al 2001) and 120 minutes (Pagliosa et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This obstruction involves occlusion of the cranial mesenteric artery (CMA) (Ritz et al 2005, Gao et al 2006, Santos et al 2008, Jiang et al 2011, Ben et al 2012, Boybeyi et al 2014 or the CMA and cranial mesenteric vein (Guimarães et al 2002, Tang et al 2010 or the extramural peri-intestinal marginal artery (PIMA) (Guan et al 2009). Some authors report that vascular clamping is the best method of ischemic applicability due to promoting the same occlusive situation in all animals and because of the similarity in clinical situations (Ribeiro & Yoshida 2005, Freitas et al 2009a, 2009b.…”
Section: Introductionmentioning
confidence: 99%